Emotional Intelligence in Digital Age: Meaning, Importance and Strategy or Emotional Growth Through Stories - Panjwani, Diya (International Journal of Psychosocial Rehabilitation, 2020)
Emotions are the impulsive responses in the circumstances around us. This is absolutely a conservative thought that one should lock away the emotions at work place or there shouldn’t be any display of emotions at the corporate corridors. In reality emotional make up largely determines the professional success. Emotions can prove very dangerous if exhibited in an incongruous situation. However, emotions exhibited intelligently are constructive and play pivotal role in healthy environs. The way one maintains interpersonal and intrapersonal relationships reflects one’s emotional intelligence. EI is a measure for segregating potential employees and good leaders from the rest. Thus, the analysis is done on how emotions help at work place precisely. My paper will explore the emotional growth through story method. It includes LRTW which stands for Listening, Reading, Telling, Writing stories. The first section of the paper provides an overview of Emotional Intelligence and its importance. In the second section, story method as strategy to indoctrinate EI is introduced. The key words that run through my paper are Emotions, Social skills, Eco therapy, Stories and Script therapy, must be perceived contextually. The objective of writing this paper is to provide the knowledge and necessity of Emotional intelligence at work place and to spread awareness about EI. The experience of different writers from literature is quoted for reference which is collected from various sources duly acknowledged that may provide guidelines to the digital generation.